Identification of the Biotransformation Pathways of a Potential Oral Male Contraceptive, 11β-Methyl-19-Nortestosterone (11β-MNT) and Its Prodrugs: An In Vitro Study Highlights the Contribution of Polymorphic Intestinal UGT2B17 - Namrata Bachhav; Dilip Kumar Singh; Diana L. Blithe; Min S. Lee; Bhagwat Prasad (MDPI AG, 2024)
11β-Methyl-19-nortestosterone dodecylcarbonate (11β-MNTDC) is a prodrug of 11β-MNT and is being considered as a promising male oral contraceptive candidate in clinical development. However, the oral administration of 11β-MNTDC exhibits an ~200-fold lower serum concentration of 11β-MNT compared to 11β-MNTDC, resulting in the poor bioavailability of 11β-MNT. To elucidate the role of the first-pass metabolism of 11β-MNT in its poor bioavailability, we determined the biotransformation products of 11β-MNT and its prodrugs in human in vitro models. 11β-MNT and its two prodrugs 11β-MNTDC and 11β-MNT undecanoate (11β-MNTU) were incubated in cryopreserved human hepatocytes (HHs) and subjected to liquid chromatography-high resolution tandem mass spectrometry analysis, which identified ten 11β-MNT biotransformation products with dehydrogenated and glucuronidation (11β-MNTG) metabolites being the major metabolites. However, 11β-MNTG formation is highly variable and prevalent in human intestinal S9 fractions. A reaction phenotyping study of 11β-MNT using thirteen recombinant UDP-glucuronosyltransferase (UGT) enzymes confirmed the major role of UGT2B17 in 11β-MNTG formation. This was further supported by a strong correlation (R2 > 0.78) between 11β-MNTG and UGT2B17 abundance in human intestinal microsomes, human liver microsomes, and HH systems. These results suggest that 11β-MNT and its prodrugs are rapidly metabolized to 11β-MNTG by the highly polymorphic intestinal UGT2B17, which may explain the poor and variable bioavailability of the drug.